Analysis of synovial fluid of the Capybara's stifle joints - Brombini, Giovanna C. [UNESP]; Rahal, Sheila C. [UNESP]; Bergamini, Bruno C. S. [UNESP]; Lopes, Raimundo S. [UNESP]; Santos, Ivan F. C. [UNESP]; Schimming, Bruno C. [UNESP] (Wiley, 2017)
Background: Although normal synovial fluid has been well characterized in domestic animals such as dogs, cats, horses, and cows, the available information on larger rodents is scarce. Objectives: The purpose of the study was to analyze the physical, chemical, and cytologic characteristics of the synovial fluid in stifle joints of Capybaras. Methods: Five free-ranging adult female Capybaras (Hydrochoerus hydrochaeris), weighing from 37 to 56 kg were used. Synovial fluid was obtained by aspiration of 10 stifle joints. Samples were analyzed for physical, chemical, and cytologic properties. Results: Spontaneous clotting was negative in 9 samples. Most synovial fluids had pH 8, and protein concentrations ranged from 1.6 to 3.6 g/dL. The mucin clot test was good in all 6 samples that were tested. Nucleated cell counts ranged from 140 to 508 cells/μL. Relative differential leukocyte counts demonstrated a predominance of mononuclear cells (97.6%), including 76.2% undifferentiated mononuclear cells, 18.1% macrophages, and 3.66% lymphocytes. Polymorphonuclear cells included 1.83% neutrophils and 0.2% eosinophils. Conclusion: The synovial stifle joint fluid of healthy free-ranging adult Capybaras is clear, colorless, viscous, and with chemical features and cytologic findings similar to those seen in domestic animals.
Keywords: Joint; nondomestic animal; stifle; synovia